1989
DOI: 10.1002/lsm.1900090609
|View full text |Cite
|
Sign up to set email alerts
|

Lactate dehydrogenase in laser incisions: A comparative analysis of skin wounds made with steel scalpel, electrocautery, superpulse—continuous wave mode carbon‐dioxide lasers, and contact Nd:YAG laser

Abstract: A histochemical method for demonstrating lactate dehydrogenase activity was used in addition to standard Van Gieson stain to study early alterations near wounds made in pig skin by steel scalpel, electrocautery, two modes of CO2 laser (the rapid super-pulse mode and the continuous wave mode), and contact Nd:YAG laser. The enzyme-free zone near the wounds made using the thermal knives appeared to be twice as wide as the necrotic zone observed with Van Gieson stain. In polarized light, the enzyme-free area showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
3

Year Published

1991
1991
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 3 publications
0
6
0
3
Order By: Relevance
“…Because only viable cells show the active enzyme, this method provides a sensitive way for determining the depth of tissue necrosis. This method uses a nitrotetrazolium (NBT) salt, a redox indicator that turns blue in the presence of lactic dehydrogenase [14]. Three 4-mm punch biopsies were obtained from each treatment site, frozen in dry ice, and stored at −75°C.…”
Section: Histologymentioning
confidence: 99%
“…Because only viable cells show the active enzyme, this method provides a sensitive way for determining the depth of tissue necrosis. This method uses a nitrotetrazolium (NBT) salt, a redox indicator that turns blue in the presence of lactic dehydrogenase [14]. Three 4-mm punch biopsies were obtained from each treatment site, frozen in dry ice, and stored at −75°C.…”
Section: Histologymentioning
confidence: 99%
“…Wound strength for both techniques after 14-21 days of recovery has been shown to be similar; however, until that point, wounds created with a steel scalpel blade were stronger [5,[10][11][12]13]. This finding may be attributed to the mild tissue coagulation at the edges of the wound or the increased inflammatory response caused by the Nd:YAG laser's thermal effects.…”
Section: Discussionmentioning
confidence: 72%
“…The histochemical demonstration of the LDH activity has previously been used to determine the precise extents of laser-induced lesions [17], Hukki et al [17], who also used polarized light for the examination of specimens, found that the enzyme-free zone close to the wound was twice as wide as the necrotic zone observed using van Gieson stain and light microscopy. In the present study, the histological demonstration of the LDH activity was used to determine the phase in which the regeneration began.…”
Section: Discussionmentioning
confidence: 99%